Fat but fit for the improved survival in lung cancer surgery - Bertolaccini, Luca; Calabrese, Francesca; Brandolini, Jury; Bonfanti, Barbara; Parri, Sergio Nicola Forti; Lacava, Nicola; Solli, Piergiorgio (Journal of Thoracic Disease, 2018)
“Anger as soon as fed is dead, Tis starving makes it fat.” Emily Dickinson, Poems, Second Series, 1891.